Detection of micro emboli using signal energy and discrete fourier transform / Basil Mathew Panamkuttiyil - Basil Mathew , Panamkuttiyil (2011)
A micro embolus is a plug of clot, fat, air or other material not normally found in blood that moves with flowing blood between two points in the circulation. Micro emboli have been detected with pathologies such as carotid artery disease, atrial fibrillation and also in association with implanted vascular devices, such as prosthetic heart valves or left ventricular assist devices. Conventional method for detecting the presence of emboli is done manually which is a very tedious procedure. In this case examiner needs to spend long time to detect emboli by visual or audio identification. This also can result in human errors in finding exact numbers and location of emboli. The purpose of this research was to automatically detect the presence of micro emboli signals and localize them from Trans-cranial Doppler (TCD) signals by using signal energy and Discrete Fourier Transform. Efficient detection of micro embolus helps in earlier diagnosis of stroke and for also assigning corresponding therapy. TCD signal recorded in magnetic tape digital signal with a sampling frequency of 44.1 KHz were used. Algorithms were formulated in both time and frequency domain to get efficient and accurate results. In time domain the variations in signal energy and on frequency domain difference in frequency due to presence of emboli is taken into consideration. The number of occurrences and localization of micro embolus was done based on its unique attributes framed by International Consensus on Micro Embolus Detection. Conventional detection method is used and it is compared with the results obtained using algorithm to check the accuracy. The designed algorithm was able to detect presence of emboli with considerable accuracy. Automation eliminates the tedious conventional method and also improves the accuracy by reducing human errors.